A neural circuit from paratenial thalamic nucleus to anterior cingulate cortex for the regulation of opioid-induced hyperalgesia in male rats - Peng-Fei Zhu; Xuan Wang; Bin Nie; Mei-Hong Li; Yu-Ting Li; Bo Wu; Chen-Hong Li; Fang Luo (Neurobiology of Disease)
Prolonged use of opioids can lead to increased sensitivity to painful stimuli, a condition referred to as opioid-induced hyperalgesia (OIH). However, the mechanisms underlying this contradictory situation remain unclear. This study elucidates the pivotal role of the paratenial thalamic nucleus (PT)-anterior cingulate cortex (ACC) neuronal circuit in the development of OIH in male rats. Immunofluorescence and electrophysiology experiments demonstrated aberrant activation of PT glutamatergic neurons (PTGlu) in rats with OIH. Optogenetic or chemogenetic activation of the PTGlu-ACC circuit aggravates mechanical and thermal hyperalgesia. Conversely, the inhibition of neuronal circuits showed analgesic effects. Additionally, PTGlu neurons project to both ACC pyramidal neurons and interneurons. Moreover, OIH affects the function of the ACC microcircuit, leading to decreased feedforward inhibition and an inhibitory/excitatory (I/E) imbalance in ACC pyramidal neurons. In conclusion, our findings highlighted the role of the PTGlu-ACC neuronal circuit in the development of opioid-induced hyperalgesia, suggesting that this circuit is a promising therapeutic target for addressing the side effects of opioids.